Housing as an economic object in the global dimension - Shcherbyna А. (Ways to Improve Construction Efficiency, 2020)
The article offers a view on housing as an economic object, real estate with its value characteristics. The valuation of residential real estate in global assets and in household wealth is analysed. It shows how the largest, residential housing segment of the economy is formed, which begins with the creation of residential real estate and is extended by the need for their further maintenance, repair and operation with significant funds from homeowners. Author researches the social function of housing and the impossibility of self-sufficiency in housing provision of a significant part of households in any country, the need for the formation and consideration of two subsystems of housing ownership: individual and social in various forms. The methodological and analytical part of the article analyses the valuation of residential real estate in global assets, where its share reaches more than 45%. The place of residential real estate in the wealth of households, where its share exceeds 50%, is considered. On this basis, it is proved that the largest residential segment is formed in the economy, which begins with the creation of residential real estate and is extended by the need for their further maintenance, repair and operation with significant funds from homeowners. Given the social function of housing and the impossibility of self-sufficiency of a significant part of households in any country, the need for the formation and consideration of two subsystems of housing ownership: individual and socialized in various forms. Based on the hypertrophied privatization of private housing in Ukraine, the inability of its inefficient owners to preserve and maintain it has been shown. The rational ratio between the cost of residential real estate, the volume of new construction and capital investment in repairs is demonstrated. The conclusion is made about the need and ways to transform the housing sector in Ukraine in the direction of a rational relationship between these subsystems and to ensure their viability.